2014
DOI: 10.1111/jphd.12062
|View full text |Cite
|
Sign up to set email alerts
|

Direct access to midlevel dental providers: an evidence synthesis

Abstract: The limited extent of experimental evidence regarding direct access to MLDPs contrasts with their widespread use across Europe, the United States, and the southern hemisphere. Suggestions are made for a research program to improve the evidence base for direct access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…8,69,72 The importance of lay perspectives on the quality of health services, particularly its acceptability, is increasing, 23,73,74 especially where there are plans to extend the use of skillmix. [75][76][77] Given the recent enhancement and innovation of the remit of DAs in certain countries, including the introduction of direct access, 26,78,79 it is surprising that high quality data do not exist to inform these policy decisions. Moreover, a paradox exists where quality frameworks assert the primacy of public and patient perspectives, yet policy decisions about the reorganisation and delivery of care have been made in the absence of high quality evidence of the acceptability of using DAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,69,72 The importance of lay perspectives on the quality of health services, particularly its acceptability, is increasing, 23,73,74 especially where there are plans to extend the use of skillmix. [75][76][77] Given the recent enhancement and innovation of the remit of DAs in certain countries, including the introduction of direct access, 26,78,79 it is surprising that high quality data do not exist to inform these policy decisions. Moreover, a paradox exists where quality frameworks assert the primacy of public and patient perspectives, yet policy decisions about the reorganisation and delivery of care have been made in the absence of high quality evidence of the acceptability of using DAs.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been recent policy and regulatory changes in some countries to facilitate the use of DAs, 26,71,79 high quality evidence is required to inform policy-makers and the dental profession of their legitimacy. 20,80 In addition, the dental profession, notably in the US and Canada, hotly debates DAs enhancing and innovating their skills and remit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[73][74][75][76][77][78][79] Treatment outcomes for atraumatic restorative techniques were also similar across a number of criteria for single-surface (small) and multisurface (large) restorations for DCPs and GDPs. 72 In a review of the literature on direct access, 80 DCPs were again found to perform to a similar standard as GDPs, although the evidence base found by Dyer et al 72 and Brocklehurst et al 80 was mainly descriptive with only a few experimental studies.…”
Section: Organisation Of Nhs Dentistry In Primary Carementioning
confidence: 99%
“…[49][50][51][52][53] The need for health system reform in order to support the application of enhanced skills in practice to improve patient care was identified with a continuous programme of training to be established rather than a one-off course.…”
Section: Professional Developmentmentioning
confidence: 99%